Le sida et son assurabilité : quelques considérations éthiques - Grantham, Harry (Assurances)

(untitled) (HEC Montréal, 1988)
AIDS is indeed a contemporary phenomenon which raises numerous questions in various fields and which involves a great many professionals. The author, Mr. Harry Grantham, responsible for the teaching of medical ethics at the Faculty of Medicine of Laval University, uses the medical and clinical data presently available and writes on insurance, at the ethical level, and offers concrete proposals. He concludes his article by expressing the hope that the economy and the financial world will remain sensitive to social needs and be open to new solutions.